Increasing protein supply to pregnant beef cows when energy is limited does not improve cow or calf performance - Bailey, E.A.; Titgemeyer, Evan C.; Cochran, R.C.; Jones, Timothy J.; Olson, K. C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
Pre- and postpartum deficiencies of metabolizable protein have been identified as potentially limiting to productivity of beef cows and calves. Pre-partum supplementation of forage-based diets with ruminally undegraded protein has increased weight gain and breeding performance in prior studies, but the level of ruminally degraded protein fed was not known. Feeding adequate ruminally degraded protein to beef cows maximizes the productivity of microbes in the rumen, so any benefits shown in prior work could have been attributed to increased ruminal fermentation. Our objectives were (1) to determine the value of supplementing ruminally undegraded protein when dietary ruminally degraded protein supply was estimated to be adequate to support normal ruminal fermentation, and (2) to monitor the changes in intake and digestion that precede parturition in beef cows fed low-quality, warm-season forage.
Keywords: Beef; Protein; Calf performance; Breeding; Intake; Digestion